1998
DOI: 10.1021/js970246a
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin Conjugates of Doxorubicin: Synthesis, Characterization, Cellular Uptake, and in Vitro Efficacy||

Abstract: One strategy for improving the antitumor selectivity and toxicity profile of antitumor agents is to design drug carrier systems employing suitable carrier proteins. Thus, thiolated human serum transferrin was conjugated with four maleimide derivatives of doxorubicin that differed in the stability of the chemical link between drug and spacer. Of the maleimide derivatives, 3-maleimidobenzoic or 4-maleimidophenylacetic acid was bound to the 3'-amino position of doxorubicin through a benzoyl or phenylacetyl amide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
129
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 34 publications
5
129
1
1
Order By: Relevance
“…17) Transferrin receptors were found to be more widely distributed on the tumor tissues than the normal tissues. 18) Transferrin can be exploited as a carrier of drugs, such as neocarzinostatin, 19) adriamycin, 20,21) and cisplatin. 22,23) We have previously described the covalent attachment of MMC to give TF-MMC, which aided the delivery of MMC to the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…17) Transferrin receptors were found to be more widely distributed on the tumor tissues than the normal tissues. 18) Transferrin can be exploited as a carrier of drugs, such as neocarzinostatin, 19) adriamycin, 20,21) and cisplatin. 22,23) We have previously described the covalent attachment of MMC to give TF-MMC, which aided the delivery of MMC to the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrazones play an important role in improving the antitumor selectivity and toxicity profile of antitumor agents by forming drug carrier systems employing suitable carrier proteins (Kratz et al, 1998). They also have anti-inflammatory and analgesic activity equal or close to that of aspirin (Sondhi et al, 2006).…”
Section: Isonicotinoyalhydrazone Metal Complexesmentioning
confidence: 99%
“…Transferrin has several adventages over other drug carriers. It is not an immunogenic, but is a commercially available protein [6]. The transferrin receptor (known as CD71), a type II transmembrane glycoprotein found on the surface of cells, is a protein involved in iron uptake and the regulation of cell growth [7].…”
Section: Introductionmentioning
confidence: 99%
“…The transferrin receptor (known as CD71), a type II transmembrane glycoprotein found on the surface of cells, is a protein involved in iron uptake and the regulation of cell growth [7]. The expression of transferrin receptors is significantly upregulated in a variety of malignant cells [7], so the conjugation of anticancer drugs with transferrin might aid in delivering the therapeutics directly to neoplastic cells (via receptor-mediated endocytosis) with reduced injury to normal cells [4][5][6]. A number of studies have indicated that the conjugation of doxorubicin with the serum protein transferrin significantly increased the cytotoxic effect against tumour cells both in vitro [6,8,9] and in vivo [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation